Transhumanism and Posthumanism in Twenty-First Century Narrative. - Chapman, Ana María (Open Edition Journals, 2022)
Book review of Sonia Baelo-Allué and Mónica Calvo-Pascual (editors)'s Transhumanism and Posthumanism in Twenty-First Century Narrative.”, European journal of American studies
Keywords: Literatura estadounidense; Literatura contemporánea; transhumanism; Posthumanism; contemporary north american literature